¿Es posible un mundo sin drama? Esbozo para una recuperación de la teoría del teatro postdramático (Urdimento, 2024)
The essay seeks to return to the characterization of contemporary theater as “postdramatic”, according to Hans-Thies Lehmann, but reinforcing it with a consideration of drama as the ideological core of contemporary capitalism, and finally going beyond the ideas of the German theorist to propose a strong and critical concept of the postdramatic.
Keywords: teoría teatral; drama; estética y politica; teatro posdramático